Pembangunan Aplikasi E-Commerce Pada Usaha Mikro Kecil Menengah Berbasis Web (Studi Kasus Paguyuban "Preman Super" Kota Malang) - Husniyah Lisan; Bayu Priyambadha; Achmad Arwan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The association of Preman Super is a MSMEs multiproduct in Malang City that has helped the government in improving the economy and welfare of Malang residents, especially for housewives and laborers. One of activities from Preman Super is to peddling products owned by members of Preman Super through online media by using one gate system in the management of buying and selling transactions. The weakness were found in this system which is the ordering process became inefficient because it takes a lot of time both from the side of the buyer waiting for confirmation from the seller, the admin who handles transactions between buyers and sellers, and sellers who handle orders from buyers. These problems are the basis of research to build a web-based e-commerce application for Micro, Small and Medium Enterprises (MSMEs) in order to ease the management of buying and selling transactions and can assist in managing sales and financial reports from sales. This study used a prototyping model approach with twice iterations that is built using the CodeIgniter framework, MySQL and Javascript. This system has been tested using white box testing for unit testing, black box testing for functional testing, and compatibility testing for non-functional testing. The test results of e-commerce web applications of Preman Super got 100% valid result and explained that the application can be run properly even though in different browsers, for example Google Chrome, Mozilla Firefox, Microsoft Edge, and Opera.